The reduction of cholesteryl linoleate in lipoproteins: An index of clinical severity in β-thalassemia/Hb E - Rataya Luechapudiporn (2018)
Background: Oxidative modification of lipoproteins has been reported in β-thalassemia and has been suggested to relate to atherogenesis-risk. This study focused on the change in cholesteryl esters in plasma lipoproteins under oxidative stress resulting from iron overload in β-thalassemia/hemoglobin E (β-thal/Hb E) patients. Methods: Markers of oxidative damage and cholesteryl esters (CEs) were measured in plasma and lipoproteins from 30 β-thal/Hb E patients and compared to those from 10 healthy volunteers. CEs in plasma, low-density lipoprotein (LDL) and high-density lipoprotein (HDL) were separated and identified using HPLC. Results: β-Thal/Hb E patients presented iron overload, a precipitous decrease in α-tocopherol and increased lipid peroxidation (thiobarbituric acid-reactive substances; TBARs) in both plasma and lipoproteins. Cholesteryl linoleate, the most abundant CE in lipoproteins, showed a reduction of 70% in LDL, while other CEs showed a lower reduction (50%). An inverse relationship between the cholesteryl linoleate/cholesteryl oleate ratio (CL/CO) and the degree of clinical severity suggested that the CL/CO ratio is an index of damaged lipoproteins and could be used as a pathologic marker of underlying iron overload. Good correlation of non-transferrin-bound iron (NTBI) and TBARs (r = 0.8, p < 0.01) in LDL strongly supported the contention that iron overload is responsible for initiating the lipid peroxidation in β-thal/Hb E. Conclusions: This study suggests that cholesteryl linoleate is the primary target of oxidative modification induced by NTBI in β-thal/Hb E patients and that reduction in cholesteryl linoleate in lipoproteins could be used as a severity index for β-thal/Hb E. © 2006 by Walter de Gruyter.